2011
DOI: 10.1186/1471-2458-11-766
|View full text |Cite
|
Sign up to set email alerts
|

HIV Risk and Associations of HIV Infection among men who have sex with men in Peri-Urban Cape Town, South Africa

Abstract: BackgroundThe HIV epidemic in Sub Saharan Africa has been traditionally assumed to be driven by high risk heterosexual and vertical transmission. However, there is an increasing body of data highlighting the disproportionate burden of HIV infection among MSM in the generalized HIV epidemics across of Southern Africa. In South Africa specifically, there has been an increase in attention focused on the risk status and preventive needs of MSM both in urban centers and peri-urban townships. The study presented her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 20 publications
9
101
2
1
Order By: Relevance
“…Fifty-seven percent (95%CI: 51.6; 61.8) had experienced some type of discrimination in the year prior to the interview. 43.5% reported not having told their parents about their sexual attraction to other men (95%CI: 38.2; 48.8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-seven percent (95%CI: 51.6; 61.8) had experienced some type of discrimination in the year prior to the interview. 43.5% reported not having told their parents about their sexual attraction to other men (95%CI: 38.2; 48.8).…”
Section: Resultsmentioning
confidence: 99%
“…Sexual category was associated with the result of the syphilis test (prevalence of syphilis and HIV was higher among homosexuals). The literature generally reports an association between sexual identity and risky sexual practices for HIV infection 12,29,38,42 , stigma 29 , difficult access to health services 31,43 , and HIV infection 26,43 .…”
Section: Discussionmentioning
confidence: 99%
“…In Kendall et al's [16] study in Angola for instance, 61.3 % of participants had never tested for HIV, while Vu et al [42] found that 45.1 % of their participants in Nigeria had never tested. In a study conducted in Cape Town, South Africa, Baral et al [56] found that only 6 % of HIVpositive MSM participants knew their HIV status. These findings again point to the urgent need for more widespread HIV-related interventions for MSM.…”
Section: Hiv Prevention Interventions For Msm and Male Sex Workers Inmentioning
confidence: 98%
“…(National Coalition for Gay & Lesbian Equality v. Minister of Justice, CCT 11/98 per Sachs J., para. 126-127; cited inBaral, Burrell, Beyrer, & Bekker, 2009) …”
mentioning
confidence: 98%